Heterometallic lanthanide complexes with site-specific binding that enable simultaneous visible and NIR-emission - Thornton, Matthew E.; Hemsworth, Jake; Hay, Sam; Parkinson, Patrick; Faulkner, Stephen; Natrajan, Louise S. (Frontiers in Chemistry, 2023)
Macrocyclic lanthanide complexes have become widely developed due to their distinctive luminescence characteristics and wide ranges of applications in biological imaging. However, systems with sufficient brightness and metal selectivity can be difficult to produce on a molecular scale. Presented herein is the stepwise introduction of differing lanthanide ions in a bis-DO3A/DTPA scaffold to afford three trinuclear bimetallic [Ln2Ln'] lanthanide complexes with site-specific, controlled binding ([Yb2Tb], [Eu2Tb], [Yb2Eu]). The complexes display simultaneous emission from all Ln III centers across the visible (Tb III , Eu III ) and near infra-red (Yb III ) spectrum when excited via phenyl ligand sensitization at a wide range of temperatures and are consequently of interest for exploiting imaging in the near infra-red II biological window. Analysis of lifetime data over a range of excitation regimes reveals intermetallic communication between Tb III and Eu III centers and further develops the understanding of multimetallic lanthanide complexes.